Expression of eg9 gene encoding endoglucanase GH8 derived from metagenomic DNA data of bacteria in humus around white rot fungi degrading woods, in Escherichia coli - Thi Huyen, Do; Thu Hoai, Le; Hai Dang, Nguyen; Thi Quy, Nguyen; Nam Hai, Truong (Vietnam Journal of Biotechnology, 2021)
Endoglucanase is an important enzyme participating in the hydrolysis of cellulose into oligosaccharides or glucoses can be used in a variety of industrial fields. A gene (code GL0183420 designated as eg9) of 1398 bp encoding for endoglucanase family GH8 was identified from metagenomic DNA data of bacteria in the humus surrounding wood hydrolyzed by white rot fungi. The 126 terminal nucleotides at 5' terminal of the gene encode for a signal peptide in gram-negative bacteria and the next 1269 nucleotides encode the endoglucanase GH8. In this study, the eg9 gene (lack of sequence encoding the signal peptid) coding for the mature endoglucanase was codon optimized for expression in E. coli, artificical synthesized, then inserted into pET22b(+) for gene expression in E. coli strains. Through a survey of 5 expressive strains, EG9 was overexpressed in Rosetta and C43 strains. However, at 30oC in LB medium, most of EG9 were expressed in the insoluble fraction, in which Rosetta was the best strain for synthesis of EG9. The enzyme EG9 can be overexpressed in Rosetta strain at a large range of OD600 from 0.2 to 1. After reducing the culture temperature to 25°C, 50% of EG9 was expressed in soluble fraction and exhibited good hydrolysis activity in CMC substrate on agar plate. The investigation of media showed that PE was the most suitable medium for the recombinant Rosetta strain grow and synthesize endoglucanase EG9. EG9 was well expressed at various IPTG concentrations from 0.05 to 0.9 mM. These results offer great potential for production of recombinant EG9 for enzyme properties research.